Mental health of healthcare workers during the COVID-19 pandemic - Maja Skočo; Jelena Pavlović (Biomedicinska istraživanja, 2023)
Health workers, doctors and nurses and other health staff, due to their occupation and daily exposure to stressful situations, are the most exposed to professional burnout and the dangers of numerous mental disorders. The aim of this review was to point out, based on data from recent literature, the importance and level of mental health of doctors and nurses during the COVID-19 pandemic. Mental health is influenced by various factors, from social changes and circumstances to personal experiences in society. Extended working hours, night work, shift work, responsibility when making decisions, contact with the sick, contact and care for patients in the terminal phase of the disease, care for their families, and also the professional burnout of health workers have increased the morbidity of numerous psychological disorders and psychosomatic diseases in health workers, especially during viral epidemics and pandemics. The World Health Organization advocates the thesis that the feeling of pressure in the current situation associated with the COVID-19 pandemic is normal, and that taking care of mental health is just as important as taking care of physical health.